Business Opportunities in Power Supply with Gas Engines in the Health Sector - Vokony, István; Sinkovits, Bálint; Sőrés, Péter Márk; Divényi, Dániel; Szalmáné Csete, Mária (Public Finance Quarterly, 2022)
In the research, we have developed an operational concept based on new energy generation devices, which, in addition to providing heat and electricity, guarantees uninterrupted supply locally and the sale of system services off-site. Based on international experience in the sector, the overall business concept needs to be developed for successful pilot projects. The trends in the technical-economic and regulatory environment examined show that the direction of change, with uncertain outcomes today, is unanimous: they all support the market penetration and the continued profitability of smallscale power plant devices suitable for secondary regulation. An important task is to identify unique elements in the value propositions. The aim of the research is to identify which of the factors such as realized price differential, heat-side revenues, generation utilization, optimized plant operation, scaling, etc. have an impact on the investment, operation, as well as the overall business model and profitability, and to what extent.